Understanding the Role of Language on Twitter: From Hashtag to Discourses - Daulay, Sholihatul Hamidah; Aulia, Dea Nita (General English Education, 2024)
This article delves into the intricate dynamics of language on Twitter, tracing the evolution from the simple use of hashtags to the emergence of complex discourses. The study explores how language shapes and influences the trajectory of discussions within Twitter. By analyzing the linguistic elements embedded in tweets, unravel the nuances that contribute to the formation and evolution of broader discourses on the platform. The research investigates the multifaceted role of language in shaping online conversations. From the early days when hashtags served as mere categorization tools, Twitter has transformed into a space where language plays a pivotal role in constructing and deconstructing narratives. Through a qualitative analysis of tweet content identify linguistic patterns and examine their impact on the development of larger discussions.